1990
DOI: 10.1093/infdis/162.4.932
|View full text |Cite
|
Sign up to set email alerts
|

Strain- and Donor-Related Differences in the Interaction of Mycobacterium avium with Human Monocytes and its Modulation by Interferon- 

Abstract: Mycobacterium avium is a cause of disseminated infection in AIDS patients. The pathogenicity of M. avium for human monocytes was examined in an in vitro model. Peripheral blood monocytes obtained from 13 healthy donors were precultured for 2 days before infection. Monocytes were infected with six AIDS-associated and three non-AIDS-associated strains and four strains of M. avium selected on the basis of colonial morphology. Uptake of M. avium detected by counting intracellular acid-fast bacilli differed accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 0 publications
3
34
0
Order By: Relevance
“…In the present study, as in other studies (36,40), it was found that the SmT variant SmT, LR114F, 101) generally tended to be more resistant to drugs in the broth assay, and this information is extended in the present study to show that the SmT isolates were often more resistant in the macrophage assay to drugs active against other morphological variants. Similar observations have been made with human monocytes (10,37).…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, as in other studies (36,40), it was found that the SmT variant SmT, LR114F, 101) generally tended to be more resistant to drugs in the broth assay, and this information is extended in the present study to show that the SmT isolates were often more resistant in the macrophage assay to drugs active against other morphological variants. Similar observations have been made with human monocytes (10,37).…”
Section: Discussionsupporting
confidence: 87%
“…The results presented in this report provide new evidence that IL-12 consists of p40 and p35 chains, both of which are required for bioactivity (1 (26,27), IFN-'y reduces the bacillary burden in lepromatous leprosy patients (28) and is a functional marker of murine T cells that confer adoptive immunity against tuberculosis (29,30). TNF-a augments the mycobactericidal capacity of human macrophages ( 31 ) and is essential for granuloma formation to contain murine mycobacterial infection (32).…”
Section: Discussionmentioning
confidence: 86%
“…Samples were harvested at time 0 (immediately after infection) and 7 d after infection for CFU assay. The density of monocyte monolayers as assessed by counting cell nuclei with naphthol blue black staining ( 19) was comparable between control and gp 1 20-pretreated cultures throughout the 7-d culture period.…”
Section: Introductionmentioning
confidence: 86%
“…Most M. avium growth using this experimental system is intracellular and not due to adherence ( 19 Counting ofAFB. Immediately after infection with M. avium, petri dishes were fixed with methanol and stained by Kinyoun's modified acid-fast method.…”
Section: Introductionmentioning
confidence: 94%